Surface Hydrophobicity and Functional Properties of Citric Acid Cross-Linked Whey Protein Isolate: The Impact of pH and Concentration of Citric Acid - Li, Tong; Wang, Chunyan; Li, Tianqi; Ma, Ling; Sun, Dongxue; Hou, Juncai; Jiang, Zhanmei (Molecules (Basel, Switzerland), 2018)
The effects of citric acid-mediated cross-linking under non-acidic conditions on the surface hydrophobicity, solubility, emulsifying, and foaming properties of whey protein isolate (WPI) were investigated. In this research, citric acid-mediated cross-linking could not only increase the surface hydrophobicity of whey proteins at pH 7.0 and 8.0, but it also improved its emulsifying and foaming properties. The emulsifying activity and foaming ability of WPI reached a maximum under the condition of 1% citric acid and pH 7.0. However, the solubility of WPI-CA gradually decreased with pH and the content of citric acid increased. Therefore, the cross-linking mediated by citric acid under non-acidic aqueous conditions, markedly altered the surface hydrophobicity and enhanced emulsifying and foaming properties of WPI.